The Realization of Marked Theme in Narrative Text of Secondary School Textbook (Jurnal Sosial Humaniora dan Pendidikan, 2025)
This study aimed to analyzed the realization of marked theme in narrative text. The data of this study is the narrative text in the English for Nusantara Textbook. This study applied a qualitative approach with content analysis as research design. The study found that the narrative texts in English Textbook are realized through adverbial group, prepositional phrase and linking words. This study concluded that the narrative texts in the textbook can be a model for students to create different sentence structures by putting adverbial or prepositional at the beginning of the sentence and connect ideas logically by using connectors.